Sanitary barriers as educative and preventive´s action for the control of Covid-19 dissemination in a big city at southeastern Brazil - Nathalia Sernizon-Guimarães; Maria do Carmo Barros-de Melo; Taciana Malheiros Lima-Carvalho; Jackson Machado-Pinto; Ana Otávia Ribeiro-Paiva; Karine Aparecida Ribeiro Soares Bertoni; Elisa França Chaves; Ronniel Morais-Albuquerque; Ricardo Tadeu de Carvalho; Carmem Lage-Vieira; João Eduardo dos Santos; Luís Felipe Rezende-de Almeida; et al. (Instituto Nacional de Salud Pública, 2021)
Not available.